The relationship between job satisfaction and organizational commitment among employees at Samarahan District Council, Kota Samarahan / Norazima Ali - Ali, Norazima (2016)
This research was accomplished to identify is job satisfaction and organizational commitment a connected among employees at Samarahan District Council, Kota Samarahan and to find out if they are interrelated to each other. Furthermore, the aim to do this research is to know the factors that were influencing between job satisfaction and organizational commitment among employees. On the other hand, for the scope area of this study were done in an area of Kota Samarahan, Sarawak. According to Meyer and Allen (1991), there are three dimensions of organizational commitment include, affective commitment, continuance commitment and normative commitment. According to Mowday, Steer and Porter (1982), there are several forms of commitment and it comprises the employee’s acceptance in the organization, like the aspiration to struggle for the job beside to stay on for the current job. According to Meyer and Allen (1991), affective commitment is the worker’s expression and involvement in the organization. The employees with a strong affective commitment remain working with the organization as they willing to do so (Meyer and Allen, 1991).